2017
DOI: 10.7150/jca.18744
|View full text |Cite
|
Sign up to set email alerts
|

GSK-3β suppresses HCC cell dissociation in vitro by upregulating epithelial junction proteins and inhibiting Wnt/β-catenin signaling pathway

Abstract: Glycogen synthase kinase-3β (GSK-3β) is required in the expression of epithelial junction proteins. It was found downregulated in hepatocellular carcinoma (HCC) tissues. The purpose of this study was to investigate the role of GSK-3β in modulating the metastatic behaviors of human HCC cell lines in vitro. In this study, the expression level of GSK-3β was measured in 4 human HCC cell lines, and the small interfering RNA (siRNA) vectors against or plasmids encoding GSK-3β were used to evaluate the responses of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 24 publications
(22 reference statements)
0
16
0
Order By: Relevance
“…N-cad and Vimentin are considered as pivotal mesenchymal markers, commonly used to reflect EMT [ 28 ]. In the cytoplasm, β -catenin continues binding and dissociating the cytoskeleton proteins, which promotes tumor cell migration by regulating cytoskeleton and modulating the coordinated cell–cell adhesion [ 29 , 30 ]. As our data suggested, ARG1 could promote the EMT process in HCC cells through upregulating the expression of N-cad, Vimentin, and β -catenin both at protein and mRNA levels, which was further supported by the downregulation of N-cad, Vimentin, and β -catenin and upregulation of E-cadherin in ARG1 knockdown cells.…”
Section: Discussionmentioning
confidence: 99%
“…N-cad and Vimentin are considered as pivotal mesenchymal markers, commonly used to reflect EMT [ 28 ]. In the cytoplasm, β -catenin continues binding and dissociating the cytoskeleton proteins, which promotes tumor cell migration by regulating cytoskeleton and modulating the coordinated cell–cell adhesion [ 29 , 30 ]. As our data suggested, ARG1 could promote the EMT process in HCC cells through upregulating the expression of N-cad, Vimentin, and β -catenin both at protein and mRNA levels, which was further supported by the downregulation of N-cad, Vimentin, and β -catenin and upregulation of E-cadherin in ARG1 knockdown cells.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence indicated that GSK3β mediated β-catenin phosphorylation is the key step to generate the β-TrCP-binding site for the subsequent degradation [ 35 , 52 , 53 ]. A recent study in HCC also showed that GSK-3β suppresses HCC cell dissociation in vitro by inhibiting Wnt/β-catenin signaling pathway [ 19 ]. Furthermore we found that the expression of ALX4 was positively correlated with the expression of the key members of the “β-catenin degradation complex”.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that ALX4 could suppress lung cancer progression by inducing cell apoptosis [ 18 ]. Recent studies showed its tumor-promoting or tumor-suppressive roles in HCC and ovarian cancers, indicating its diverse functions among different types of cancer [ 19 , 20 ]. Previous mice model study demonstrated that ALX4 is required for normal mammary gland morphogenesis during mouse puberty and lost expression in stromal and epithelial cells in breast tumors [ 13 , 14 ], suggesting it may be involved in the precancerous lesions of breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Mutations and the overexpression of β‐catenin are detected in HCC tumour tissues and associated with the progression of HCC . The inhibition of Wnt/β‐catenin signalling by GSK‐3β restricts the proliferation, migration and invasion of HCC cells, suggesting an important role of GSK‐3β/Wnt/β‐catenin signalling in the progression of HCC . Wnt/β‐catenin signalling has been suggested as a promising target for the treatment of HCC.…”
Section: Introductionmentioning
confidence: 99%
“…22,23 The inhibition of Wnt/β-catenin signalling by GSK-3β restricts the proliferation, migration and invasion of HCC cells, suggesting an important role of GSK-3β/Wnt/β-catenin signalling in the progression of HCC. 24 Wnt/β-catenin signalling has been suggested as a promising target for the treatment of HCC. Despite the fact that the main components of the canonical Wnt/β-catenin signalling pathway have been characterized, the precise regulatory network of Wnt/β-catenin signalling transduction remains partially understood.…”
mentioning
confidence: 99%